Effects of alpha-linolenic acid and essential amino acids on the proliferation and differentiation of C2C12 myoblasts - Dongjie Zhou; Xiao-Han Li; Song‑Hee Lee; Geun Heo; Xiang-Shun Cui (The Korean Society of Animal Reproduction and Biotechnology, 2022)
Alpha-linolenic acid is an important polyunsaturated fatty acid that exhibits anticancer, anti-inflammatory, and antioxidative effects. In this study, we investigated the protective effects of alpha-linolenic acid on the cell proliferation and differentiation of C2C12 cells under essential amino acid-deficient conditions. Different concentrations of alpha-linolenic acid and essential amino acids were added to the growth and differentiation media. The concentrations of 10 μM of alphalinolenic acid and 2% essential amino acid were chosen for subsequent experiments. Supplementation with alpha-linolenic acid and essential amino acids improved the proliferation and differentiation of C2C12 cells and significantly increased the mRNA levels of catalase, superoxide dismutase, B-cell lymphoma-2, and beclin-1 as well as the protein levels of PPARγ coactivator-1α compared to those in the controls. Moreover, supplementation with alpha-linolenic acid and essential amino acids reduced the levels of phosphorylated H2A.X variant histone, Bcl-2-associated X, p53, and light chain 3 during C2C12 cell proliferation, and increased the expression levels of myogenic factors 4 (myogenin) and 5 during C2C12 cell differentiation. Overall, we determined that alpha-linolenic acid and essential amino acids maintained the cell proliferation and differentiation of C2C12 cells via their anti-oxidative, anti-apoptotic, and anti-autophagic effects.